Diseño de un plan de mantenimiento preventivo para el uso adecuado de los equipos torno BD -920N / taladro JET 016065 empleando el diagnóstico de fallas y el método FMEA (2022)
The failure analysis on industrial equipment allows making decisions and establishing maintenance plans; applying preventive actions that improve the service provided by the machines. Based on the failures found in the equipment of the mechanical laboratory of the Antonio Nariño University in Neiva, a preventive maintenance plan was designed for the BD 920 N lathe and the JET 016065 arbor drill. Using explanatory research as a methodol ogy, we started with a diagnosis and FMEA risk level, allowing us to describe the causes for which the equipment in question became inoperable. As a result, preventive maintenance was carried out, using forms such as equipment life sheets, technical data s heets, lubrication charts and inspection forms. We concluded with the repair of the equipment, highlighting that the failures that caused the deterioration were caused by the lack of lubrication and maintenance routines.